Pengaruh Arus Pengelasan Terhadap Kekerasan Hasil LasPelat Baja Karbon S45c Dengan Proses SMAW - Tulus Swasono; Emon Azriadi (Jurnal Sains dan Ilmu Terapan, 2018)
Welding is a process of joining two or more metals which is widely applied in the industrial world. To get good welding results, it is necessary to choose the right amount of current. In this study, variations in the amount of current used were 60 A, 70 A and 80 A for welding S45C carbon steel plates, using the SMAW welding method. The results of the welding were then tested for hardness using the Rockwell HRB scale method in the weld metal, HAZ, and base metal areas. From the results of this study, the hardness value in the weld metal area was higher than the hardness value in the HAZ and base metal areas. And a good current used in welding S45C carbon steel plates is a welding current of 80 A.